Self-polarization Effect and Electron-phonon Interaction Contributions in Forming of Electron Energy Spectrum of PbI2 Nanofilm Embed in E-MAA Copolymer - O.V. Pugantseva; V.M. Kramar (Журнал нано- та електронної фізики)
The paper describes results of theoretical study of the role of self-polarization effect and electron-phonon interaction in the formation of the energy spectrum of electrons in semiconductor flat nanofilm. Concrete calculations are performed using the example of 2H-PbI2 nanofilm embed in the methyl-acrylic acid copolymer (E-MAA). It was found that contribution of self-polarization's effect to the value of the electron energy in ultrathin nanofilms is more than from the interaction with polarizing optical phonons.